2013
DOI: 10.2527/jas.2011-5057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linseed addition on the expression of some lipid metabolism genes in the adipose tissue of young Italian Simmental and Holstein bulls1

Abstract: The objective of this trial was to determine the effect of breed and long-term dietary linseed addition on composition of fatty acids and expression of some genes involved in the lipid metabolism within subcutaneous (s.c.) adipose tissue of young bulls. Italian Simmental and Holstein bulls (n=16/breed) were fed a corn silage-grass hay diet with or without 8% (DM basis) whole ground linseed. Inclusion of linseed, rich in α-linoleic acid (C18:3n-3), increased (P<0.05) the proportions of linolelaidic (C18:2n-6tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
5
22
0
Order By: Relevance
“…No statistically significant correlation was found between the ∆9 desaturase index and total lipid content. These results are in agreement with the findings of Corazzin et al (2013), which showed no differences in the ∆9 desaturase index when comparing animals with different subcutaneous fat deposits, but in contrast with the findings of Jiang et al (2008), who reported a positive correlation between ∆9 desaturase activity and the marbling of beef. Level of significance:* P <0.05; ** P <0.01;***P <0.001; ns: not significant.…”
Section: Resultssupporting
confidence: 92%
“…No statistically significant correlation was found between the ∆9 desaturase index and total lipid content. These results are in agreement with the findings of Corazzin et al (2013), which showed no differences in the ∆9 desaturase index when comparing animals with different subcutaneous fat deposits, but in contrast with the findings of Jiang et al (2008), who reported a positive correlation between ∆9 desaturase activity and the marbling of beef. Level of significance:* P <0.05; ** P <0.01;***P <0.001; ns: not significant.…”
Section: Resultssupporting
confidence: 92%
“…Also, the latter authors hypothesized that feeding FP can increase Δ9 desaturase activity. In general, previous studies reported that diet can influence the activity and expression of Δ9 desaturase . However, Δ9 desaturase is involved in the synthesis of the main conjugated linoleic acid (CLA) isomer (CLA c 9, t 11) .…”
Section: Resultsmentioning
confidence: 99%
“…In general, previous studies reported that diet can influence the activity and expression of Δ9 desaturase. 39,40 However, Δ9 desaturase is involved in the synthesis of the main conjugated linoleic acid (CLA) isomer (CLAc9,t11). 41 In the present trial, no difference in CLA level was found between experimental groups (P > 0.05).…”
Section: Animal Performance Carcass and Meat Characteristicsmentioning
confidence: 99%
“…SCD1 inserts the cis-9 double bond in stearic acid to make oleic acid. In fact, Hiller et al (2011) reported an increase in SCD1 gene expression in bovine muscle after feeding bulls a grain-based diet, while Dervishi et al (2011) and Corazzin et al (2013) reported that SCD gene expression could be reduced by grazing.…”
Section: Discussionmentioning
confidence: 99%